IMPLEMENTASI TEKNIK PENGERITINGAN VERTIKAL UNTUK MENINGKATKAN HASIL IKAL RAMBUT ALAMI - Aulia Sonda Silalahi; Julia Evani Br Ginting; Nurul Ubaiya Rambe; Ramalia Hutasoit; Asrah Rezki Fauzani; Mutia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Hair perming is a hair styling technique aimed at creating curls or waves to enhance aesthetic value. One commonly used method is the vertical design technique, which involves wrapping the hair in a vertical direction following its natural fall. This study aims to examine the implementation process of the vertical perming technique and the results obtained in hair styling practice. The method used is descriptive observation through direct observation during the perming process. The results show that the vertical design technique produces curls that are more natural, soft, and well-directed, while providing balanced volume without making the hair appear overly bulky. In addition, this technique creates a more elegant look that aligns with modern hair styling trends. Therefore, the vertical perming technique can be used as an alternative method to achieve natural and aesthetically pleasing hairstyles.